DESAIN MEDIA PEMBELAJARAN SEJARAH BERBASIS AUGMENTED REALITY DI SMA N 1 KOTO XI TARUSAN PESISIR SELATAN - Tiara Adha Putri; Supratman Zakir; Zulfani Sesmiarni; Wedra Aprison (Universitas Pahlawan Tuanku Tambusai, 2022)
Based on the results of observations and interviews with the class X history teacher at SMA N 1 Koto XI Tarusan Pesisir Selatan. The author concludes that teachers have not maximized the use of technology in learning that tend to use blackboard media, besides that many teaching aids from history learning are damaged. What makes students only rely on verbal learning from the teacher, so students feel bored quickly when learning takes place and have difficulty understanding the material taught by the teacher. Therefore, the authors design learning media based on Augmented Reality so that it can be an alternative learning media. The purpose of this research is to produce an Augmented Reality-based supporting media design that is valid, practical and effective. Research on the design of Augmented Reality-based historical learning media at SMA N 1 Koto XI Tarusan Pesisir Selatan uses the Research and Development (R&D) method using the Luther-Sutopo version of the Multimedia Development Life Cycle (MDLC), which consists of six stages, namely concept. , design (design), material collection (material collection), assembly (manufacture), testing (testing) and distribution (distribution). The product test used in this study is the validity test using the Aiken's V statistical formula, the practicality test using the kappa moment, and the effectiveness test using the Richard R. Hake statistical formula (G-Score). The resulting product is a history learning application created using Unity 3D 2019.1.9f1(64-bit). The results of the product test that the author did get a validity test from 3 validators getting a value of 0.94 with a valid category, the practicality test from 3 history teachers getting a value of 0.95 with a very high category, and the effective test of 10 students getting a score of 0 ,84 with effective category. Keywords: Learning media, History, Augmented Reality